Profile severe acute respiratory syndrome cases obtained by a public health reference laboratory (Research, Society and Development, 2021)
Objective: To analyze the profile of notified SARS cases and results obtained by a Public Health Reference Laboratory. Methodology: This is a cross-sectional study, developed from the notification forms and notified results of SRAG obtained through the LACEN-GO Surveillance Nucleus. The Epi info 3.5.4 software was used to transcribe the results, analyze the variables contained in the notification form and the Chi-square test (x2). Results: 691 SRAG notification forms and their reported results were analyzed. The average age of the cases was 33 years, the main biological sample was the secretion of the oro and nasopharynx and for the identification of the viral etiology, the RT-PCR was used. Regarding the epidemiological profile, most of the cases were female, non-pregnant, had an education higher than 8 years, were not vaccinated and there was a need for the use of antiviral drugs. The main signs and symptoms were cough, fever and respiratory distress. The main comorbidity was chronic cardiovascular disease. There was a need for hospitalization, the main radiological pattern found was the interstitial infiltrate and the intensive care unit was used. The main viral etiologic agent diagnosed was the Influenza A / H1N1pdm09 virus. Conclusion: The epidemiological surveillance of Influenza through SARS Notification, including surveillance of SG in sentinel units, is an important tool for public health and has become the fundamental factor for the prevention, containment, surveillance and therapeutic management of patients.